2010
DOI: 10.1002/cbm.767
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in re‐offending among psychiatrically examined Swedish offenders

Abstract: Our study is limited by sample size, although it included all women referred to the specialist forensic psychiatric service over 2 years, but it does indicate that differences between men and women in this situation are likely, and worthy of further study. The only way of achieving adequate sample sizes is likely to be through multi-centre collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Possibly treatment was more accessible to women than men during the study period and thereby increasing females’ probability of survival. Furthermore, women are less likely to be incarcerated [24,25,37] and less likely to re-offend [38,39]. It could be that gender differences in incarceration and treatment increased females’ probability of survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly treatment was more accessible to women than men during the study period and thereby increasing females’ probability of survival. Furthermore, women are less likely to be incarcerated [24,25,37] and less likely to re-offend [38,39]. It could be that gender differences in incarceration and treatment increased females’ probability of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the first weeks after prison release are associated with increased mortality risk [35-37]. Women are less likely to be incarcerated [24,25,37], and less likely to re-offend [38,39]. …”
Section: Introductionmentioning
confidence: 99%
“…This is supported by the argument that different risk factors may be of different significance within different populations, e.g. the role of mental illness appears to differ when applied to the general population compared with offenders and to female compared with male offenders (Alm et al, 2010;Chang et al, 2015).…”
Section: Violence Risk Assessment Of Offendersmentioning
confidence: 94%
“…Alm et al identified gender differences in the patterns of reoffending of MDOs after discharge from forensic psychiatric services [ 20 ], but it was noted that its findings should be interpreted with caution due to the study’s small sample size (only 13 women and 23 men in the sample reoffended). Another study on the subject included only 24 patients with reconvictions [ 9 ]; small sample sizes is a common problem in forensic psychiatric research.…”
Section: Introductionmentioning
confidence: 99%